Komunitas Department of Sociology and Anthropology, Faculty of Social Sciences, State University of Semarang (UNNES)C7 Building 1st Floor Campus Sekaran, Gunungpati, Semarang 50229 (2010)
KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE (p-ISSN 2460-7312, e-ISSN 2460-7320) is nationally accredited by the Directorate of Higher Education Indonesia based on SK NO. 58/DIKTI/Kep./2013. KOMUNITAS: INTERNATIONAL JOU
RNAL OF INDONESIAN SOCIETY AND CULTURE is formerly known as Jurnal Komunitas (P-ISSN 2086 - 5465, E-ISSN 2337 - 5426) Jurnal Komunitas is indexed by DOAJ, Google Scholar, JournalTOC,Ebsco and every article is given a unique DOI. Though Jurna
l Komunitas is full English journal starting from its Vol 6 (2) edition, the journal still accept submission manuscripts written in Bahasa Indonesia. Authors should submit their proposed research papers through ONLINE SUBMISSION menu provided in t
his page (click here) Notification upon the result of your the article submission and review may appear in the SPAM of your email. Please check your email regularly. Authors should use reference manager (for example Mendeley, Zotero, Endnote
) to organize the references in the manuscript.